Donor coordination and specialization: did the Paris Declaration make a difference? - Nunnenkamp, Peter; Öhler, Hannes; Thiele, Rainer (Review of world economics, 2013)
We assess whether bilateral and multilateral donors of foreign aid specialized and coordinated their activities with other donors as agreed in the Paris Declaration of 2005. We account for donor heterogeneity, varying aid priorities and recipient characteristics in order to isolate changes in donor behaviour over time. Recent shifts in aid priorities, such as the rising importance of general budget support, have reduced the fragmentation of aid. Nevertheless, our results reveal that aid fragmentation persisted after the Paris Declaration and coordination among donors has even weakened.
Gesehen am 29.11.2021